Group Guidance Through Internalization of Indigenous Knowledge Values to Reduce Student Aggressiveness at Madrasah Tsanawiyah - Anna Ayu Herawati; Vira Afriyati; Fadil Maiseptian; Chici Pratiwi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students in the learning process often experience social problems such as rampant aggressive behaviour. An environment that rarely instils local cultural values can trigger the erosion of ethics and morals. Through the cultivation of local wisdom, it is hoped that it will be able to reintroduce students to the cultural values that belong to Indonesia. Efforts to overcome student aggressiveness can be made with group guidance through the internalization of local wisdom values. This study aimed to describe the differences in student aggressiveness before and after being given a treatment of group guidance services through the internalization of local wisdom values (Indigenous Knowledge). The method used is pre-experimental with the One-Group Pretest-Posttest Design approach. The population of this study were all students of class IX at a Madrasah Tsanawiyah. Samples were taken by purposive sampling technique. Data collection techniques using a questionnaire with a Likert scale. The data analysis technique using the T-test showed a value of t = 10.774 and sig (2-tailed) 0.000, meaning 0.000 ˂ 0.05. Based on score data, group guidance through the internalization of indigenous knowledge values is effective in reducing student aggressiveness.